2007
DOI: 10.1021/jf063638o
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Malolactic Fermentation by Oenococcus Oeni and Lactobacillus Plantarum to the Changes in the Nonanthocyanin Polyphenolic Composition of Red Wine

Abstract: The changes in the nonanthocyanin phenolic composition during red wine malolactic fermentation carried out spontaneously and by four different starter cultures of the species Oenococcus oeni and Lactobacillus plantarum were examined to determine whether differences in nonanthocyanin polyphenolic compounds could be attributed to the lactic acid bacteria (LAB) strain that performs this important step of the wine-making process. The polyphenolic compounds were analyzed by high-performance liquid chromatography wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 36 publications
9
56
1
Order By: Relevance
“…In fact it seems clear that the decrease in concentration of caftaric, coutaric and fertaric acids, and the increase in concentration of caffeic, p-coumaric and ferulic acids are linked to lactic acid bacteria metabolism, as previously stated by Hernández and co-workers [33] that have shown that transcaftaric and trans-coutaric acids are substrates of lactic acid bacteria witch can exhibit cinnamoyl esterase activities during malolactic fermentation, increasing the concentration of hydroxycinnamic acids.…”
Section: Discussionsupporting
confidence: 55%
“…In fact it seems clear that the decrease in concentration of caftaric, coutaric and fertaric acids, and the increase in concentration of caffeic, p-coumaric and ferulic acids are linked to lactic acid bacteria metabolism, as previously stated by Hernández and co-workers [33] that have shown that transcaftaric and trans-coutaric acids are substrates of lactic acid bacteria witch can exhibit cinnamoyl esterase activities during malolactic fermentation, increasing the concentration of hydroxycinnamic acids.…”
Section: Discussionsupporting
confidence: 55%
“…In relation to flavonols, the MLF seemed to involve the hydrolysis of quercetin-3-O-glucoside (higher content before MLF) into quercetin (higher content after MLF). These results agreed with previous studies about the transformations of phenolic compounds during MLF in red wines (Herná ndez et al, 2007).…”
Section: Phenolic Compoundssupporting
confidence: 93%
“…The interaction between LAB and phenolic compounds is influenced by various factors including the strain of LAB (Hernández et al, 2007;García-Ruiz et al, 2008) and the type and concentration of phenolic compounds present in the wine (Stead, 1993;Reguant et al, 2000;García-Ruiz et al, 2008). Due to this interaction, phenolic compounds can affect the occurrence as well as rate of MLF (Vivas et al, 1997).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Due to this interaction, phenolic compounds can affect the occurrence as well as rate of MLF (Vivas et al, 1997). Polyphenolic compounds can be transformed by LAB and clear differences in the phenolic content as a result of MLF have been reported (Hernández et al, 2007). The main compounds that can be transformed by different LAB include hydroxycinnamic acids and their derivatives, flavonols and their glycosides, flavanol monomers and oligomers, as well as trans-resveratrol and its glucoside (Hernández et al, 2006(Hernández et al, , 2007.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation